2018
DOI: 10.1080/15384101.2018.1475829
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: MiR-29a-5p inhibits proliferation and invasion and induces apoptosis in endometrial carcinoma via targeting TPX2

Abstract: EC: Endometrial cancer; 3'-UTR: 3'-untranslated regions; TPX2: target protein for Xenopus kinesin-like protein 2; TCGA: the Cancer Genome Atlas; UCEC: uterine corpus endometrial carcinoma; CCK-8: cell counting kit-8; OD: optical density; FCM: flow cytometry; EMT: epithelial-mesenchymal transition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 31 publications
0
36
0
Order By: Relevance
“…Other genes significantly associated with unfavourable prognosis included ARL4C , TUBB4A and TPX2 . Previous immunohistochemical studies have found similar results for ARL4C and TPX2 in EC [ 220 , 221 ], whereas no reports exist to date on TUBB4A in the endometrium. ARL4C has been shown to interact with TERF2 and TERF2IP [ 222 ], whilst TUBB4A interacts with TINF2 [ 160 ].…”
Section: Discussionmentioning
confidence: 70%
“…Other genes significantly associated with unfavourable prognosis included ARL4C , TUBB4A and TPX2 . Previous immunohistochemical studies have found similar results for ARL4C and TPX2 in EC [ 220 , 221 ], whereas no reports exist to date on TUBB4A in the endometrium. ARL4C has been shown to interact with TERF2 and TERF2IP [ 222 ], whilst TUBB4A interacts with TINF2 [ 160 ].…”
Section: Discussionmentioning
confidence: 70%
“…Gluz et al found that KIF2C which acted as a proliferation marker was risk factors for the pathological complete response (pCR) rate of TNBC. TPX2 had been proved to be overexpressed in many malignant tumors and promoted tumor deterioration [ 39 , 40 ]. In breast cancer cells, TPX2 affects cancer cell colony formation, proliferation, and invasion through PI3K/AKT signal pathway and promotes tumor progression [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Liu et al9 validated that miR-29a suppressed viability, migration and invasion via TRAF4/Akt Signaling in glioma. Even in endometrial carcinoma, miR-29a impaired the viability and invasion, and induced the apoptosis through targeting TPX2 10. Thus, we hypothesize that miR-29a may play a role in cervical cancer.…”
Section: Introductionmentioning
confidence: 85%